EFFECT OF DIETARY SUMAC AND FIBROLYTIC ENZYMES ON SOME PRODUCTIVE AND HAEMATOLOGICAL TRAITS OF LAMBS - L. I. Hadi; M. J. Al-Saadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The research was conducted at the Animal Farm of the University of Baghdad’s College of Veterinary Medicine to assess the effect of dietary grind seeds of Sumac and Exogenous Fibrolytic Enzymes(EFE) on some productive and haematological traits of Awassi male lambs from the period 1/2/2021 to 1/6/2021. Twenty-four Awassi male lambs with 3-4 months of age, and divided into four groups based on body weight . Dietary treatments were as following: G1 (control) equal nourished concentrate diet at the rate of 2.5% body weight (B.W) with alfalfa hay daily, G2 was fed on the similar diet as control group and was given 15g/head dried grind seeds of Rhus Coriaria daily with diet, G3 was fed on the similar diet that was presented in G1 with 5g/head of (EFE) daily, G4 was fed on the same diet in G1 with a 15g/head dried grind seeds of Rhus Coriaria and 5g/head of EFE. The results of live body weight, monthly weight gain and feed conversion ratio showed significant increased (p<0.05) of G2, G3, G4 comparing with G1.Also values of Hemoglobin, showed significance exceed (p<0.05) of G2, G3, G4 compared with G1. Values of RBCs showed that G4 significance exceed (p<0.05) other groups from the 3rd month to the end of experiment, while G3 and G2 significance exceed G1 at the last month of experiment. Values of total WBCs showed non-significance difference among different groups. In conclusion, these result showed the significant effect of Rhus Coriaria and (EFE) consumption on some productive and heamatological aspects of Awassi male lambs.